Computational design and analysis of LiFePO4 battery thermal management system (BTMS) using thermoelectric cooling/thermoelectric generator (TECTEG) in electric vehicles (EVs) - Hameed M.M.; Mansor M.B.; Azau M.A.M.; Alshara A.K. (Elsevier Ltd, 2024)
The best option for addressing the issue of rising carbon dioxide levels, which is the primary cause of global warming, currently involves using electric vehicles (EVs). The successful production of EVs can be attributed to batteries. However, one major issue lies in the rise in temperatures for the battery system of EVs. Therefore, a good battery thermal management system (BTMS) is necessary. Several traditional and non-traditional types of these systems are available. BTMSs for EVs have utilized thermoelectric cooling (TEC) and thermoelectric generator (TEG). The current research introduces a hybrid BTMS that combines thermoelectric materials with forced air. While the use of thermoelectric materials in BTMS is not a new concept, this approach offers a novel solution. In the current study, the thermoelectric cooler (TEC) and thermoelectric generator (TEG) are combined into a single unit. While TECs have long been used in BTMS, the new addition of TEGs allows for the conversion of lost heat from the TEC's hot surface into a reverse voltage that powers both the TEC and TEG. Additionally, the TEG helps to reduce the overall temperature of the battery container by converting heat into a potential difference, as previously mentioned. Simulation of the single battery cell and the full BTMS is realized using the ANSYS 2021R1 software. A single battery cell and BTMS utilize 6,197,879 and 12,697,173 numbers of mesh, respectively. The introduced BTMS was utilized in the current study to decrease the maximum surface temperature of a single battery cell by approximately 7 C. 2023 Elsevier Ltd